Mining user generated content - Moens, Marie-Francine 1957-; Li, Juanzi; Chua, T. S. 1955- (CRC Press, Taylor & Francis Group, 2014)
Originating from Facebook, LinkedIn, Twitter, Instagram, YouTube, and many other networking sites, the social media shared by users and the associated metadata are collectively known as user generated content (UGC). To analyze UGC and glean insight about user behavior, robust techniques are needed to tackle the huge amount of real-time, multimedia, and multilingual data. Researchers must also know how to assess the social aspects of UGC, such as user relations and influential users. Mining User Generated Content is the first focused effort to compile state-of-the-art.
"A Chapman & Hall book.". - Includes bibliographical references (pages 329-396). - Online resource; title from PDF title page (ebrary, viewed February 26, 2014)
Keywords: Data mining; User-generated content; Data Mining; Exploration de données (Informatique); Contenu créé par l'utilisateur; COMPUTERS; General